Implications of supplemental microbial phytase and essential oils (Thymus vulgaris L. and Mentha pulegium L.) on carcass traits, meat organoleptic and antioxidant status in broilers - Ghalandari, Eslam; Safamehr, Alireza; Nobakht, Ali; Mehmannavaz, Yousef; Mahdavi, Saman (Journal of the Hellenic Veterinary Medical Society, 2022)
An experiment was carried out to study the influence of herbal essential oils (Thymus vulgaris L and Mentha pulegium L.) and microbial phytase on carcass traits, meat organoleptic and antioxidant status in broilers. Three hundred and eighty-four male broilers (Ross -308) were used in factorial arrangements with eight treatments includes (0 and 200 mg/kg thyme essential oil), (0 and 200 mg/kg Mentha essential oil), (0 and 500 IU/kg microbial phytase) and 4 replicates (12 chicks per replicate) according to a CRD and in three experimental periods include: starter 1 to 10 days, grower 11 to 24 days and finisher 25 to 42 days. Regarding the effects of experimental treatments on carcass traits, the use of thyme and mentha essential oils increased the percentage of abdominal fat (P<0.05). The use of thyme essential oil significantly increased the levels of blood superoxide dismutase (SOD) and glutathione peroxidase (GPX) (P<0.05). Regarding the effects of experimental treatments on meat organoleptic, the use of thyme essential oil increased the overall acceptance of chicken meat (P<0.05). The use of essential oils, although it leads to an increase in antioxidant parameters, also leads to an improvement in meat quality.